O código He-Man: narrativas forjadas em um banco de dados analógico - Bozzetti, Augusto Ramos (Universidade do Vale do Rio dos Sinos, 2019)
This research is concerned with the way in which cartoons are organized as a survival strategy in the television environment, where an aggressive demand for content, combined with severe limitations of budget ans deadlines, provoke the emergence of a kind of code of programming similar to what happens in digital media, although this happens in an analogical and handmade way. Based on excavations that are part of the media archeology methodology, we try to analyze images produced for the animation series "He-Man and the Masters of the Universe" in order to understand how this particular object operates based on the discontinuity and modularity of its elements, in the sense of constructing its narratives from a very limited database that feeds a virtually infinite number of combinatorial options to give rise to its contents. That way, we seek to understand the unique nature of animation cinema, as opposed to the traditional cinema made with real actors and locations, conceptualizing the cinematographic art and stressing the theoretical assumptions that are focused on the media objects that emerge from the era of technical reproducibility, following the Industrial Revolution track.
Keywords: Desenhos animados; Ambiente televisivo; Mídias digitais; Cinema de animação; Cartoon; TV environment; Digital media; Animation cinema; ACCNPQ::Ciências Sociais Aplicadas::Comunicação